(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
• Afratis N.A., Selman M., Pardo A. et al. Emerging insights into the role of matrix metalloproteases as therapeutic targets in fibrosis. Matrix Biol 2018;68–69:167–79. DOI: 10.1016/j.matbio.2018.02.007 • Allen TK, Feng L, Grotegut CA, Murtha AP. Progesterone receptor membrane component 1 as the mediator of the inhibitory effect of progestins on cytokine-induced matrix metalloproteinase 9 activity in vitro. Reprod Sci. 2014 Feb;21(2):260-8; • Allen TK, Nazzal MN, Feng L, Buhimschi IA, Murtha AP. Progestins Inhibit Tumor Necrosis Factor α-Induced Matrix Metalloproteinase 9 Activity via the Glucocorticoid Receptor in Primary Amnion Epithelial Cells. Reprod Sci. 2019 Sep;26(9):1193-1202; • Amubieya O, Todd JL, Neely ML, Kaner RJ, Lasky JA, Namen A, Hesslinger C, Palmer SM, Weigt SS, Belperio JA. Associations of circulating matrix metalloproteinases and tissue inhibitors of matrix metalloproteinases with clinically relevant outcomes in idiopathic pulmonary fibrosis: Data from the IPF-PRO Registry. PLoS One. 2024 Oct 17;19(10):e0312044 • Bonhomme O. André B., Gester F. et al. Biomarkers in systemic sclerosis-associated interstitial lung disease: review of the literature. Rheumatology (Oxford) 2019;58(9):1534–46. DOI: 10.1093/ rheumatology/kez • Cai N, Cheng K, Ma Y, Liu S, Tao R, Li Y, Li D, Guo B, Jia W, Liang H, Zhao J, Xia L, Ding ZY, Chen J, Zhang W. Targeting MMP9 in CTNNB1 mutant hepatocellular carcinoma restores CD8+T cell-mediated antitumour immunity and improves anti-PD-1 efficacy. Gut. 2024 May 10;73(6):985-999; • Chiu KL, He JL, Chen GL, Shen TC, Chen LH, Chen JC, Tsai CW, Chang WS, Hsia TC, Bau DT. Impacts of Matrix Metalloproteinase-9 Promoter Genotypes on Asthma Risk. In Vivo. 2024 Sep-Oct;38(5):2144-2151 • Craig VJ, Zhang L, Hagood JS, Owen CA. Matrix metalloproteinases as therapeutic targets for idiopathic pulmonary fibrosis. Am J Respir Cell Mol Biol. 2015 Nov;53(5):585-600; • Deng L, Ouyang B, Tang W, Wang N, Yang F, Shi H, Zhang Z, Yu H, Chen M, Wei Y, Dong J. Icariside II modulates pulmonary fibrosis via PI3K/Akt/β-catenin pathway inhibition of M2 macrophage program. Phytomedicine. 2024 Jul 25;130:155687; • Kayumova Yu.D., Tajikhodzhayeva Yu.K. Experimental model of chronic obstructive pulmonary disease with tobacco smoking in the study of membrane-destructive processes // Bulletin of the Association of Pulmonologists of Central Asia. 2020; issue 18 (No.1-4), pp.22-26. • Long L, Dai X, Yao T, Zhang X, Jiang G, Cheng X, Jiang M, He Y, Peng Z, Hu G, Tao L, Meng J. Mefunidone alleviates silica-induced inflammation and fibrosis by inhibiting the TLR4-NF-κB/MAPK pathway and attenuating pyroptosis in murine macrophages. Biomed Pharmacother. 2024 Sep;178:117216.; • Mahalanobish S, Saha S, Dutta S, Sil PC. Matrix metalloproteinase: An upcoming therapeutic approach for idiopathic pulmonary fibrosis. Pharmacol Res. 2020 Feb;152:104591 • Matsumoto H, Fujita Y, Asano T, Matsuoka N, Temmoku J, Sato S, Yashiro-Furuya M, Watanabe H, Migita K. T cell immunoglobulin and mucin domain-3 is associated with disease activity and progressive joint damage in rheumatoid arthritis patients. Medicine (Baltimore). 2020 Oct 30;99(44):e22892.; • Moss BJ, Ryter SW, Rosas IO. Pathogenic Mechanisms Underlying Idiopathic Pulmonary Fibrosis. Annu Rev Pathol. 2022 Jan 24;17:515-546; • Richeldi L, Collard HR, Jones MG. Idiopathic pulmonary fibrosis. Lancet. 2017 May 13;389(10082):1941-1952; • Spagnolo P, Kropski JA, Jones MG, Lee JS, Rossi G, Karampitsakos T, Maher TM, Tzouvelekis A, Ryerson CJ. Idiopathic pulmonary fibrosis: Disease mechanisms and drug development. Pharmacol Ther. 2021 Jun;222:107798; León-Román F, Valenzuela C, Molina-Molina M. Idiopathic pulmonary fibrosis. Med Clin (Barc). 2022 Aug 26;159(4):189-194. English, Spanish • Todd JL, Vinisko R, Liu Y, Neely ML, Overton R, Flaherty KR, Noth I, Newby LK, Lasky JA, Olman MA, Hesslinger C, Leonard TB, Palmer SM, Belperio JA; IPF-PRO Registry investigators. Circulating matrix metalloproteinases and tissue metalloproteinase inhibitors in patients with idiopathic pulmonary fibrosis in the multicenter IPF-PRO Registry cohort. BMC Pulm Med. 2020 Mar 14;20(1):64; • Xia Q, Du Z, Chen M, Zhou X, Bai W, Zheng X, Lin L, Zhao Y, Ding J, Wu Z, Zou H, Wang S, Xu L, Li E, Wu B. A protein complex of LCN2, LOXL2 and MMP9 facilitates tumour metastasis in oesophageal cancer. Mol Oncol. 2023 Nov;17(11):2451-2471